Preliminary Report on Dialect Attitudes in Austrian and Slovene Carinthia - Grant H Lundberg (Slovenski Jezik - Slovene Linguistic Studies, 2019)
This paper is a preliminary analysis of an internet-based questionnaire on dialect attitudes and perceptions conducted in Slovene-speaking areas in Austrian and Slovene Carinthia. The survey largely confirmed expectations. Large majorities on both sides of the border claimed to use and value the local dialect. Lower percentages in Austrian Carinthia claimed proficiency in the local dialect and that the youth of Austrian Carinthia primarily spoke the local dialect. Overall a relatively large percentage of respondents from Carinthia claimed the local dialect was dying, 35% in Slovene Carinthia and 75% in Austrian Carinthia. Respondents claimed that the local dialect is being replaced by the colloquial standard language or, on the Austrian side of the border, by German. It appears likely that the local dialects in Carinthia are being leveled toward the standard language rather than toward the regional dialect. These are not positive indicators for dialect maintenance, especially in Austrian Carinthia.